A Prospective Study of the Incidence of Retinopathy of Prematurity in China: Evaluation of Different Screening Criteria - Qiuping Li; Zonghua Wang; Ruijuan Wang; Hongyi Tang; Haihua Chen; Zhichun Feng (Journal of Ophthalmology)
To investigate the incidence of Retinopathy of Prematurity (ROP) in Beijing, North China, and to evaluate the effectiveness of different ROP screening criteria, we conducted a prospective cohort study in a single-neonatal intensive care unit (NICU). A total of 2997 premature infants with birth weight (BW) ≤ 2000 g and/or gestational age (GA) ≤ 34 weeks had completed ROP screening. ROP was diagnosed in 356 (11.9%) infants. The mean GA was 30.46 ± 1.98 weeks and the mean BW was 1477.35 ± 371.29 g. Of the 59 (2.0%) infants receiving treatment, the mean GA was 29.37 ± 2.10 weeks, and the mean BW was 1240.80 ± 330.71 g. The incidence of ROP declined from 14.7% in 2009 and 11.1% in 2010 to 9.5% in 2011. The United Kingdom (UK) criteria could reduce the screening number by 40.8%, and 3 infants with type I ROP needing treatment were missed, but none in 2011. The United States (US) criteria could reduce the screening number by 66.5%, and 10 infants with type I ROP needing treatment were missed, including one in 2011. So the UK criteria may be appropriate for screening of ROP in our NICU in 2011. Future multisite epidemiologic studies are required to establish suitable ROP screening criteria in China.